2017
DOI: 10.1074/jbc.m117.780072
|View full text |Cite
|
Sign up to set email alerts
|

Role of lysosomal channel protein TPC2 in osteoclast differentiation and bone remodeling under normal and low-magnesium conditions

Abstract: The bone is the main storage site for Ca and Mg ions in the mammalian body. Although investigations into Ca signaling have progressed rapidly and led to better understanding of bone biology, the Mg signaling pathway and associated molecules remain to be elucidated. Here, we investigated the role of a potential Mg signaling-related lysosomal molecule, two-pore channel subtype 2 (TPC2), in osteoclast differentiation and bone remodeling. Previously, we found that under normal Mg conditions, TPC2 promotes osteocla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Similarly, knockdown of TPCs in sea star oocytes showed defected embryo development due to debilitated Ca 2+ signalling [ 17 ]. Another study reported that TPC2 mediates osteoclastogenesis [ 18 ]. This finding is consistent with previous studies that identified a role for NAADP/TPC2-induced Ca 2+ signals in neuronal and skeletal muscle differentiation [ 16 , 19 , 20 ].…”
Section: Trends In Functional Studies Of Tpcsmentioning
confidence: 99%
“…Similarly, knockdown of TPCs in sea star oocytes showed defected embryo development due to debilitated Ca 2+ signalling [ 17 ]. Another study reported that TPC2 mediates osteoclastogenesis [ 18 ]. This finding is consistent with previous studies that identified a role for NAADP/TPC2-induced Ca 2+ signals in neuronal and skeletal muscle differentiation [ 16 , 19 , 20 ].…”
Section: Trends In Functional Studies Of Tpcsmentioning
confidence: 99%
“…Given the many physiological and pathophysiological roles that TPC2 plays as outlined above, our data suggest that individuals with different TPC2 variations will likely show different susceptibilities to various diseases. Indeed, certain TPC2 polymorphisms appear to be correlated with bone mineral density (G734E, loss-of-inhibition) [35] and inversely correlate with type 2 diabetes mellitus (M484L, gain-of-function) [36], conditions previously associated with TPC2 function [23][24][25]37]. Beyond its association with diseases, the functional spectra of TPC2 also appear of interest pharmacologically.…”
Section: Discussionmentioning
confidence: 99%
“…At steady-state Mg 2+ levels, siRNA-mediated knockdown of Tpcn2 has been shown to impair OC differentiation and bone resorption in vitro. Conversely, under low Mg 2+ culture conditions, OC formation was accelerated suggesting that Tpcn2 functions to regulates OC differentiation and activity in response to circulating Mg 2+ levels (Notomi et al, 2012(Notomi et al, , 2017.…”
Section: Tpcn2mentioning
confidence: 99%